The Effect of William Flexion Exercise on Low Back Pain in Pottery Artisans - Maruli Taufandas; Anatun Aupia; Muh. Jumaidi Sapwal; Dina Alfiana Ikhwani; Nandang DD Khairari (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
The activities performed by individuals continuously and the presence of heavy loads during physical activities can cause pain in the lower back. The occurrence of lower back pain can interfere with activities during daily work, the pain felt makes the sufferer uncomfortable in moving parts of the body, namely the back and waist areas. Researchers will answer the question, "How does William Flexion Exercise affect low back pain in pottery craftsmen?" with a focus on a group of pottery craftsmen. With the Pre Experiment: One Group Pretest and Posttest Design. This study aims to determine the effects of William Flexion Exercise on LBP in pottery craftsmen for 4 weeks, focusing on a group of workers who have never been studied. The population in this study were 43 people. Total sampling technique with a sample size of 43 respondents. The intervention was carried out for four weeks with a duration of 2 William Flexion exercises every week, the time needed for each meeting was 45 minutes, by choosing and agreeing on the implementation day together so that all respondents were present when the intervention was carried out. While the instruments used were the William Flexion Exercise SOP, William Flexion Exercise leaflet and NRS which were used to calculate the level of pain, pain measurements were carried out in the first and last weeks of the intervention by the researcher by asking the pain scale felt from 0-10, and respondents chose a number according to the level of pain felt before and after the intervention. The statistical test used was the Wilcoxon Sign Test. The statistical test used was the Wilcoxon Sign Test. According to the findings of this study, William excersise was shown to have an impact on low back pain (p value <0.05).